THE ROLE OF MUSLIM ENTREPRENEURS TO BECOME SOCIOPRENEURSHIP IN THE IMPLEMENTATION OF ZAKAT SHARING THROUGH DISTRIBUTED GOODS IS STUDIED THROUGH ONTOLOGY, EPISTEMOLOGY, AND AXIOLOGY APPROACHES - Sabila Azzahra; Nandang Ihwanudin (STIESA Press, 2021)
Philosophy of Science is a branch of science that can solve problems that occur in society that is studied through science. Currently, the philosophy of science studies a lot about how the economy develops, including currently there is an important role for sociopreneurs in supporting the Islamic economy. Philosophy examines the basis of why sociopreneurs are the pillars of agents of change in eradicating poverty that occurs in a country.